0.5–50 GHz dielectric characterisation of breast cancer tissues. Issue 13 (10th June 2015) - Martellosio, A.; Pasian, M.; Bozzi, M.; Perregrini, L.; Mazzanti, A.; Svelto, F.; Summers, P.E.; Renne, G.; Bellomi, M.
Abstract : Cancer affects a significant percentage of people, and early detection techniques are important for prompt and effective treatment. The use of microwave frequencies to achieve non‐invasive and non‐destructive cancer detections is currently under investigation by several research groups. In this frequency range, the dielectric properties of the biological tissue determine the interactions of the tissue with electromagnetic fields. Knowledge of the dielectric properties of both the normal and the malignant human tissues is therefore a fundamental starting point. A dielectric spectroscopy system, based on the use of a reflectometry setup, was used to perform an extensive experimental campaign on fresh surgical specimens. The measurement system allowed achieving a broadband dielectric characterisation of biological tissues up to 50 GHz, thus including millmetre‐wave (mm‐wave) frequencies. In the case of breast tissues, the results showed that the malignant and normal tissues exhibit significantly different complex dielectric permittivities of up to 50 GHz, due to their respective high and low water content. This permittivity difference is well detectable, and this paves the way to new screening methods based on mm‐wave imaging systems.